PENGARUH RELATIONSHIP MARKETING DAN RELATIONSHIP QUALITY TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PRODUK PARFUM MULEGH DI PURWOKERTO - Akbar, Ilham (Indonesian Journal of Strategic Management, 2018)
The research entitled â€œThe Influence of Relationship Marketing and Relationship Quality Towards Customer Loyalty with Customer Satisfaction as The Intervening Variable on Mulleg Perfume Product in Purwokertoâ€ aims to determine the impact of relationship marketing and relationship quality towards customer satisfaction and customer loyalty and to determine whether customer satisfaction could become the intervening variable. The hypothesis of this research is the relationship marketing has negative effect towards customer satisfaction, the relationship marketing has positive effect towards customer loyalty, the relationship quality has positively effect towards customer satisfaction, the relationship quality has positively effect towards the customer loyalty, and the customer loyalty could be able to mediate the influence of relationship marketing and relationship quality toward customer loyalty.Â  The analysis method that used on this research is the structural equation modeling.The results show that the relationship marketing has positive and significant effect towards customer satisfaction. It will increase the customer satisfaction of Mulleg Aromatic perfume product in Purwokerto. The relationship quality has positive and significant effect towards customer satisfaction, so it will increase the customer satisfaction of Mulleg Aromatic perfume product in Purwokerto. The relationship marketing has positive and significant effect towards customer loyalt. It will increase the customer loyalty of Mulleg Aromatic perfume product in Purwokerto. The relationship quality has positive and significant effect towards the customer loyalty. The Customer Satisfaction has positive and significant effect towards customer loyalty. The customer satisfaction could mediate the influence of relationship marketing towards the customer loyalty on Mulleg Aromatic perfume product in Purwokerto. The customer satisfaction could mediate the influence of relationship quality towards the customer loyalty of Mulleg Aromatic perfume product in Purwokerto.Â Keywords : Relationship Marketing , Relationship Quality , Customer Satisfaction and Customer LoyaltyÂ